The role of mammalian Sirtuin 6 in cardiovascular diseases and diabetes mellitus - Wu, Kehan; Wang, Yaqiao; Liu, Runmin; Wang, Hao; Rui, Tao (Frontiers in Physiology, 2023)
Cardiovascular diseases are severe diseases posing threat to human health because of their high morbidity and mortality worldwide. The incidence of diabetes mellitus is also increasing rapidly. Various signaling molecules are involved in the pathogenesis of cardiovascular diseases and diabetes. Sirtuin 6 (Sirt6), which is a class III histone deacetylase, has attracted numerous attentions since its discovery. Sirt6 enjoys a unique structure, important biological functions, and is involved in multiple cellular processes such as stress response, mitochondrial biogenesis, transcription, insulin resistance, inflammatory response, chromatin silencing, and apoptosis. Sirt6 also plays significant roles in regulating several cardiovascular diseases including atherosclerosis, coronary heart disease, as well as cardiac remodeling, bringing Sirt6 into the focus of clinical interests. In this review, we examine the recent advances in understanding the mechanistic working through which Sirt6 alters the course of lethal cardiovascular diseases and diabetes mellitus.